Tahap Penguasaan Kemahiran Menulis Jumlah Feeliah (Ayat Verbal) Dalam Kalangan Pelajar Universiti - Asmuni Zumrah; Nazipah Mat Shaid @ Md. Said; Radziah Ismail; Rosni Samah (Universiti Sains Islam Malaysia, 2026)
International Conference of Language & Education (iLEC2025): Empowering Language and Education to Develop Madani Generation in the Era of Artificial Intelligence (AI) 17 & 18 November 2025 Organized by Universiti Sains Islam Malaysia